Žena v tradičnej kultúre Slovenska: menštruácia, panenstvo, materstvo (so zameraním na nečistotu a tabu) - Kamila Beňová (AntropoWebzin, 2010)
The main thematic line of the article is the topic of women in the traditional culture of Slovakia. The study provides a brief overview of issues in social status and roles of women in the context of economic and cultural development of Slovak traditional rural society. In the next phase draws attention to the three selected phenomena of a female life, closely associated with the biological characteristics of women: menstruation, virginity and motherhood. These three phenomena look as socio-cultural phenomena, focusing mainly on their reflection in the system of values and system of rituals in traditional culture. With the main focus, to highlight the aspect of pollution (uncleanness) and taboo, with these phenomena directly related. Final part of the study is based on defining the pollution and taboo as cultural universals and anthropological categories, and then attempts to link these approaches with those selected knowledge about traditional culture of Slovakia. The study tries to synthesize, to analyze and partly to reinterpret the “old” informations in new context by using theoretical anthropological concepts, for example classical approach 'sacred – profane’ (É. Durkheim), symbolical approach of ' purity and pollution ' (M. Douglas), the symbolism of right and left hand (R. Hertz), the concept of intermediarity (Sh. B. Ortner). This all with using a feminist perspective and suggestion on phenomenon of ambivalence related specifically with all aspects of studied topic.